Dynamic associations between frailty and cognition over 4 years: a population-based study on adults aged ≥50 from 12 European countries - de Maio Nascimento, Marcelo (2024)
© 2024 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).